1996
DOI: 10.1108/09596119610108617
|View full text |Cite
|
Sign up to set email alerts
|

Employee perceptions of the hotel sector in the People’s Republic of China

Abstract: With the ever-critical travelling public now venturing throughout China, not only does China need hotel staff, it needs staff who are trained to international standards. Looks at job satisfaction indicators for the hotel sector in China as perceived by local employees. Also examines the disparity between what staff expect and what they actually think they get in the way of satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Research indicates that employees' evaluation of job characteristics affecting their job satisfaction and working behaviour often comprises several variables, including selfactualisation (Maslow, 1970), participation (Spinelli and Canavos, 2000;Kovach, 1987), recognition (Huyton and Sutton, 1996), pride (Arnett et al, 2002), advancement (Wong et al, 1999), fairness (Adams, 1965), the work itself (Hackman and Oldham, 1980) and working conditions (Huyton and Sutton, 1996;Herzberg, 1982). This helps explain how the workplace influences job satisfaction.…”
Section: Researchermentioning
confidence: 98%
See 1 more Smart Citation
“…Research indicates that employees' evaluation of job characteristics affecting their job satisfaction and working behaviour often comprises several variables, including selfactualisation (Maslow, 1970), participation (Spinelli and Canavos, 2000;Kovach, 1987), recognition (Huyton and Sutton, 1996), pride (Arnett et al, 2002), advancement (Wong et al, 1999), fairness (Adams, 1965), the work itself (Hackman and Oldham, 1980) and working conditions (Huyton and Sutton, 1996;Herzberg, 1982). This helps explain how the workplace influences job satisfaction.…”
Section: Researchermentioning
confidence: 98%
“…This is consistent with the finding of Arnett et al (2002) that there is a positive relationship between pride in an organisation and job satisfaction. In addition, factors such as better working conditions, recognition and prestige are described as 'satisfiers' by Huyton and Sutton (1996). The ISO 14001 environmental award can thus be considered an internal marketing tool for enhancing the job satisfaction of employees.…”
Section: Recognition Via Isomentioning
confidence: 98%
“…A large portion of the population in smaller cities may never have seen a living non-Chinese person. Huyton and Sutton (1996) studied hotel employee perceptions of expatriate managers compared to local managers. Among all of the staff surveyed, it was found that attitudes toward``foreigners'' varied according to the degree of staff exposure to such visitors; and the perceived national characteristics of the visitors.…”
Section: Current Chinese Culturementioning
confidence: 99%
“…Conventional wisdom proposed in academic and professional journals is that empowering employees anywhere, globally, leads to improvements in employee satisfaction at work and enhances relationships with customers, suppliers, other employees, supervisors and management (Fawcett et al, 2004; Huyton and Sutton, 1996). In considering the ways of empowering employees, the theorists have found evidence demonstrating its link with autonomy and prospect for self-determination by encouraging the individuals to decide how to carry out the job (Pearce et al, 2003; Sims and Manz, 1996) and seeking employee participation in decision making (Manz and Sims, 1987).…”
Section: Hypothesis Developmentmentioning
confidence: 99%